Environmental Assessment procedures addressing resource efficient land use: The role of learning and options in framing ‘land‘ as an environmental factor. A comparative analysis of case studies in England and Germany. - Repp, Annegret (My University, 2020)
Basierend auf Forschungssträngen zu einer ressourceneffizienten Flächennutzung untersucht die Arbeit, ob und inwieweit Aspekte des zu definierenden Schutzguts gegenwärtig Berücksichtigung in Umweltprüfverfahren finden. Eine Dokumentenanalyse ausgewählter Umweltprüfberichte wird dazu mit leitfadengestützten Experteninterviews verknüpft. Diese Analyse wird mit der Frage verbunden, welche Anpassungs- und Entwicklungsbedarfe für Fläche als separates Schutzgut identifiziert werden können, verknüpft mit Fragen nach der Rolle von Bewertungsunsicherheiten sowie von Bestimmungsfaktoren für Lernprozesse im Rahmen von Umweltbewertungsverfahren. Diese Fragestellungen werden anhand eines vergleichenden Ansatzes mit Fallstudien aus Deutschland und England bearbeitet. Dabei liegt der Fokus auf den ehemals erheblich schrumpfenden, mittlerweile aber wachsenden und durch Reurbanisierungstendenzen gekennzeichneten, mittleren Großstädten Liverpool und Leipzig, die durch vergleichbare und kontrastierende (ländlich geprägte) Fälle ergänzt werden. Die Arbeit fokussiert dabei auf den Landnutzungssektor Wohnen in Umweltprüfverfahren für kommunale Landnutzungsplanung (englische Local Plans; deutsche Flächennutzungs- und Bebauungspläne).

As an integral part of plan making procedures, Strategic Environmental Assessment (SEA) aims to systematically identify and evaluate environmental impacts at an early planning phase. With the implementation of the revised EIA Directive (2014/52/EU), the integration of ‘land‘ as a separate environmental factor, as a first step into project-related Environmental Impact Assessment (EIA), is required. With regard to chances related to a more concise consideration of land as a resource in decision-making procedures and based on strands of research on resource efficient land use, this PhD research has scrutinized if and to what extent aspects of the environmental factor to be defined are currently considered in environmental assessment procedures (EA). For that purpose, a document analysis of selected environmental reports is combined with semi-structured expert interviews. This analysis is connected with an investigation into what requirements for adaptation can be established for land as a separate environmental factor. This is linked to questions on the role of assessment uncertainties as well as on determining factors for learning in the context of EA. These issues are approached by a comparative perspective with case studies from Germany and England. The focus is on two major cities; Liverpool and Leipzig, both being characterised by reurbanisation and growth tendencies after considerable shrinkage processes throughout the 20th century. They are supplemented by both, comparable and contrasting (rural) cases. The study focuses on the housing land use sector in EA for municipal land use plans (English Local Plans; German comprehensive and binding land use plans).
Umweltprüfverfahren und ressourceneffiziente Flächennutzung: Die Rolle von Lernprozessen und Optionen zur Ausgestaltung von "Fläche" als Umweltfaktor. Eine vergleichende Analyse von Fallstudien in England und Deutschland.
Keywords: Planungsprozess; Umweltverträglichkeitsprüfung; Flächenplanung; Planfeststellung; Ressourceneffizienz; Flächeninanspruchnahme; Umweltprüfung; Reurbanisierung; Expertenbefragung; Internationaler Vergleich; Fallstudie; Städtevergleich